2021
DOI: 10.37496/rbz5020200097
|View full text |Cite
|
Sign up to set email alerts
|

Orange essential oil in the diet of broilers: performance, organ biometrics, bone characteristics, and intestinal morphometry

Abstract: Non-ruminantsFull-length research article Orange essential oil in the diet of broilers: performance, organ biometrics, bone characteristics, and intestinal morphometry ABSTRACT -Growth performance, organ biometrics, bone characteristics, and intestinal morphometry were evaluated in broilers fed a diet containing orange (Citrus sinensis L.) essential oil. A completely randomized design was used, with five treatments with orange essential oil (0, 100, 200, 300, and 400 mg kg −1 diet) and six replications with 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Although no direct effects were observed for villus height and crypt depth separately, a lower VH:CD was observed for the BEM diet when compared with the BXS diet. The BXS diet led to a desirable VH:CD, as longer villi and shallower crypts represent greater nutrient absorption capacity and lower energy expenditure with cell renewal in the intestine, respectively (Souza et al, 2021). This finding may be associated with the mechanisms of action of prebiotics, glucans, β-glucans, and MOS, and constituents of yeast cell wall since both BX and BXM diets did not affect the jejunal epithelium.…”
Section: Discussionmentioning
confidence: 90%
“…Although no direct effects were observed for villus height and crypt depth separately, a lower VH:CD was observed for the BEM diet when compared with the BXS diet. The BXS diet led to a desirable VH:CD, as longer villi and shallower crypts represent greater nutrient absorption capacity and lower energy expenditure with cell renewal in the intestine, respectively (Souza et al, 2021). This finding may be associated with the mechanisms of action of prebiotics, glucans, β-glucans, and MOS, and constituents of yeast cell wall since both BX and BXM diets did not affect the jejunal epithelium.…”
Section: Discussionmentioning
confidence: 90%
“…The broilers supplied with lemon or orange peel essential oil, either alone or in combination, had signi cantly greater (P < 0.01) body weight and weight gain than the control group [4/]. Souza et al [52] revealed that birds who received the highest dose (400 mg/kg) of orange essential oil had higher bone density and body weight at day 21. The observed effects were due to improved digestion and nutrition absorption physiological mechanisms, as evidenced by an increase in villus height [52].…”
Section: Introductionmentioning
confidence: 99%
“…Souza et al [52] revealed that birds who received the highest dose (400 mg/kg) of orange essential oil had higher bone density and body weight at day 21. The observed effects were due to improved digestion and nutrition absorption physiological mechanisms, as evidenced by an increase in villus height [52]. The amount of glycoprotein in chickens fed with salinomycin reduced by 28.7%; while it increased by 38.1% in the essential oil group.…”
Section: Introductionmentioning
confidence: 99%